Effects of different anionic surfactants on methane hydrate formation. (1st December 2015) - Wang, Fei; Jia, Zhen-Zhen; Luo, Sheng-Jun; Fu, Shan-Fei; Wang, Lin; Shi, Xiao-Shuang; Wang, Chuan-Shui; Guo, Rong-Bo
Abstract: In this work, the effects of anionic surfactants on methane hydrate formation were studied. For comparison, three anionic surfactants with the same carbon chain but different head groups, sodium dodecyl sulfonate (SDSN), sodium dodecyl sulfate (SDS) and sodium dodecyl benzene sulfonate (SDBS) were used. SDBS was detected to form micelles under hydrate formation conditions, while SDSN and SDS precipitated before micelles were formed. As a result, concentrations of SDSN and SDS did not show obvious influence on the promotion effect to methane hydrate formation, while the concentration of SDBS significantly affected the promotion effect because of the micelle effect. When SDSN and SDS were used hydrates grew upwards on the reactor wall due to the relatively narrow contact angle of the surfactant solutions on the reactor sidewall, while SDBS led to the hydrates formed mainly in the bottom of the reactor as a result of the relatively wide contact angle. In addition, SDSN and SDS led to much higher growth rate in comparison to SDBS due to the upward growth of hydrates on the reactor sidewall. Graphical abstract: Highlights: Molecular structure of surfactants affects the promotion of hydrate formation. Contact angle of solution on reactor wall influences hydrate growth pattern. Hydrate growth rate was significantly dependent on the growth pattern.